The Issues and Aspects of Women Empowerment: Feministic Perspectives - Mahara, Bishnu Bahadur (Journal of Durgalaxmi, 2022)
This article attempts to draw on the conceptual understanding of women empowerment primarily focusing on its major aspects. Empowerment enables women to acquire knowledge, skills, and techniques which will help them in their personal and social growth as well as foster their sensitivity towards problems in society. Women Empowerment refers to the creation of an environment for women where they can make decisions of their own for their benefit as well as for society. The issues of women and their empowerment are explored and interpreted using qualitative methodology highlighting feminism as a critical approach. Employing both description and content analysis as major methodological tools, the writer discusses on the social, economic, cultural, educational, political, and psychological aspects of women empowerment from feministic perspectives with an aim to familiarize the women with the basic concepts of empowerment so that it can help them increase and improve their strength in these various domains and build up confidence to create a just society based on equality, freedom and justice.